Fine Mapping of Clubroot Resistance Loci CRA8.1 and Candidate Gene Analysis in Chinese Cabbage (Brassica rapa L.) - Wang, Yanyan; Xiang, Xianyu; Huang, Fan; Yu, Wenlin; Zhou, Xueqing; Li, Baojun; Zhang, Yunyun; Chen, Peng; Zhang, Chunyu (Frontiers in Plant Science, 2022)
Clubroot is caused by Plasmodiophora brassicae, which threatens Brassicaceae crop production worldwide. In recent years, there has been an outbreak and rapidly spread of clubroot in many major cruciferous crop producing areas of China. In this study, we identified a cabbage material DW with different resistant capability from Huashuang5R (H5R) and Huayouza62R of Brassica napus, which are currently used as main resistant cultivars for clubroot management in China. We used a next-generation sequencing-based bulked segregant analysis approach, combined with genetic mapping to identify clubroot resistant (CR) genes from F1 segregant population generated from a cross between the DW (CR) and HZSX (clubroot susceptible). The CR locus of DW (named CRA8.1) was mapped to a region between markers A08-4346 and A08-4853, contains two different loci CRA8.1a and CRA8.1b after fine mapping. The CRA8.1b loci contains a fragment of 395kb between markers A08-4624 and A08-4853 on A08 chromosome, it is responsible for the resistance towards PbZj and PbXm isolates. However, together with CRA8.1a, a 765kb region between markers A08-4346 and A08-4624, then can it confer resistance towards PbXm+. Finally, through expression analysis between resistant and susceptible materials, two genes encoding TIR-NBS-LRR proteins (BraA08g039211E and BraA08g039212E) and one gene encoding an RLP protein (BraA08g039193E), was identified to be the most likely CR candidates for the peculiar resistance in DW.